Scientific-Methodological Foundations Of Organization And Management Of Methodical Work In Pre-School Educational Organizations - Olimov Sodiq Anvar o‘g‘li (Genius Publishing Group, 2024)
This article reveals the content of effective organization and management of methodological work in preschool educational organizations, the opinions of foreign scientists on methodological work, the subjects of methodological work, the system of methodological work in preschool educational organizations and the maintenance of the pedagogical community through the organization of methodological work
Keywords: Methodical work; methodical work management; system